ТАЛАБАЛАРДА МИЛЛИЙ ҚАДРИЯТЛАРНИНГ ИЖТИМОИЙ – ПСИХОЛОГИК АСОСЛАРИНИ ЎРГАНИШ - Рўзиқулова, А.Т. (SCIENCE and SOCIETY, 2024)
Author presents one of the problems as the value system on the basis of multidisciplinary development of modern society. It is describedMualic psychologist, philosopher. For educators, positive factors corresponding to the system of values inherent in the student are indicative of their opinion.